Accessible Heritage Tourism Through Universal Design: A Case Study of Peneleh, Surabaya - Sumiarsa, Fitri Fadhilah (Politeknik Negeri Bandung, 2025)
Peneleh Village, the oldest settlement in Surabaya, is a heritage area rich in historical and architectural value, offering considerable potential as a cultural tourism destination in East Java. Within the scope of sustainable tourism development, accessibility is a crucial element for ensuring inclusivity, comfort, and equal opportunities for all visitors. This study investigates the current state of accessibility in Surabaya's Old Town through universal design, prioritizing usability, safety, and clarity in public spaces without discrimination. A qualitative descriptive method was adopted, incorporating field observations, in-depth interviews with local stakeholders and tourists, and a review of heritage planning documents and regulatory frameworks. Findings indicate that many infrastructure elements in Peneleh Village do not comply with universal design standards. Out of 35 assessed indicators, only 22.86% were fully implemented, 11.43% were partially implemented, and 65.71% were not implemented—highlighting a significant gap in accessibility provision. Key issues include uneven pedestrian pathways, inadequate visual signage, and a lack of inclusive public facilities. The study presents strategic recommendations to enhance accessibility and reposition Peneleh as a user-centered and inclusive heritage destination. Improving accessibility through universal design enriches visitor experience and contributes to more sustainable and equitable cultural tourism.